Pengendalian Kualitas dalam Perencanaan Produksi Menggunakan Alat Bantu Seven Tools di Perusahaan Konstruksi - Hermawan, Fachrezi Rizki; Safariyani, Eva (Industrika : Jurnal Ilmiah Teknik Industri, 2024)
Increasingly fierce competition in the business world encourages companies to further develop ideas for effective and efficient ways to achieve predetermined goals. Many factors influence the success of achieving company goals. One of the most important forces that supports the achievement of company goals and increases company growth in the market is quality or quality score. Product or service quality control is critical to ensuring customer satisfaction and business success. One of the quality control tools is "Seven Tools" or Seven Quality Control Tools. The seven tools method is used for the production quality control process with the aim of solving various problems faced regarding the quality of a product. Types of defects found in cold room products at PT. There are 3 Pendawa Cipta Sakti, namely `: Glue doesn't stick, scratches on the coil, and holes in the styrofoam. Based on observations from graphs on histograms and Pareto diagrams, the most dominant type of defect is glue not sticking, therefore a cause and effect diagram for the type of defect glue not sticking is made. Keywords: Manufacturing, Quality Control, Seven tools